Effect of size and geometry on strength values and MOE of selected hardwood species. Issue 3 (27th May 2017) - Schlotzhauer, P.; Nelis, P. A.; Bollmus, S.; Gellerich, A.; Militz, H.; Seim, W.
Abstract: The total hardwood timber stock of German forests is fast growing. The lack of knowledge concerning test standards, product standards and sorting criteria makes it difficult to expand the processing and marketing of hardwoods into the field of construction usage. Strength and stiffness data derived from small, defect-free specimens do mostly exist, but in order to be able to insert hardwoods into building applications, data derived from real size specimens is needed. Subsequently, the results of these two different specimen categories need to be correlated and the so-called size effect needs to be quantified and qualified. This paper aims to analyze the size effect of defect-free compression, bending and tensile specimens for the six European hardwood species maple ( Acer spp. ), birch ( Betula pendula ), beech ( Fagus sylvatica ), ash ( Fraxinus excelsior ), oak ( Quercus spp. ) and lime ( Tilia spp. ) . They are tested exclusively parallel to grain. Regarding the compression strength for maple, birch and ash, the specimen dimensions did not influence the compression strength value. For beech, oak and lime, it was observed that compression strength increased as the specimen volume was increased. The bending strength of all species decreased as the specimen dimensions increased. Concerning the tensile strength, a clear statement on whether dimensions influence the tensile strength value is not possible. Further research with adjusted specimen sizes, specimen shapes and machine set-ups is needed. Regarding the compression and bending MOE, in most cases, the dimensions did not influence the MOE values. In tensile testing, MOE values differed significantly for the different specimen sizes. Whether these differences were due to slightly different test set-ups in the different sizes or a true size effect could not be answered conclusively.